Processos de inserção de analfabetos e semi-alfabetizados no mundo da cultura escrita (1930-1950) - Ana Maria Galvão de Oliveira (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This work is part of a broader research effort that aims to (re)construct the reading/listening public of cordel literature, between 1930 and 1950, in the State of Pernambuco, north-eastern Brazil. In particular, it has the objective of identifying how was the insertion of illiterate or semi-illiterate people in literacy practices. The ABC letters, school textbooks, comic books, police novels and almanacs were the most popular readings of the majority of the public investigated in the research. Some factors seem to contribute for the diversity of forms of contact with the objects of the lettered culture world and their usage, among them, the urban experience, gender, professional occupation and the basic domain of reading ability.